Short- and long-term effects of Covid-19 pandemic on health care system for individuals with eating disorders - Boltri, Margherita; Brusa, Federico; Apicella, Emanuela; Mendolicchio, Leonardo (Frontiers in Psychiatry, 2024)
Introduction The Covid-19 pandemic and its consequences have negatively impacted the incidence of EDs, determining a substantial burden on patients, caregivers and healthcare systems world-wide. This literature review aims to investigate the short- and long-term effects of the pandemic on care provider systems, exploring the possibility of “rethinking” ED care programs. Methods Records were systematically (following the PRISMA guidelines) identified through PubMed, Google Scholar and Scopus searching. Results The Covid-19 pandemic led to an abrupt and substantial increase in pediatric and adolescent ED visits and hospital admissions. Despite a decline in the second-year post-onset, absolute visit volumes remained elevated relative to pre-pandemic levels. Barriers to access specialist ED care have emerged, including socio-economic status and a lack of public outpatient services. Consequently, this situation has prompted healthcare providers to explore innovative bridge plans and multidisciplinary telehealth solutions to face such challenges. Discussion Challenges in insurance shifts, treatment disruptions and discharge planning underscore the need for comprehensive strategies in ED care. Overall, our findings highlight the importance of adopting multidisciplinary approaches, implementing location-specific plans, and integrating telehealth to effectively address the evolving challenges posed by the pandemic and enhance the efficiency of ED specialist care programs.